Literasi Keuangan dan Tantangan Ekonomi: Membekali Mahasiswa untuk Menghadapi Krisis Finansial - Nurisman, Husain; Putri, Novita Delima; Manurung, Lengsi; Zeinora, Zeinora; Suprapto, Hugo Aries (Journal of Economics, Bussiness and Management Issues, 2025)
This research is motivated by the low financial literacy of students which has an impact on their inability to face the economic crisis. The aim of this research is to determine students' financial literacy and their needs in facing a financial crisis.  Qualitative methods were used with data collection techniques in the form of semi-structured interviews with 10 students at a university in Jakarta and documentation.  Data analysis was carried out thematically. The research results show that students' financial literacy is still inadequate, especially in terms of understanding investment, risk management and protection against financial fraud. Students need practical entrepreneurship training, access to reliable information, and applicable training to improve their financial literacy.  It is recommended that higher education institutions develop innovative curricula that combine theory and practice and provide financial counseling services.  Further research needs to be conducted to explore the implementation of effective financial literacy programs for students.